2022
DOI: 10.12998/wjcc.v10.i6.1843
|View full text |Cite
|
Sign up to set email alerts
|

Systematic nursing interventions in gastric cancer: A randomized controlled study

Abstract: BACKGROUND Scientific and effective nursing methods can effectively mitigate negative emotions in patients. Related studies have shown that systematic nursing interventions are beneficial in enhancing the self-efficacy and self-care abilities of patients and improving their physical and mental state, thereby alleviating their fatigue and improving their quality of life. AIM To explore the effects of systematic nursing intervention on cancer-related fatigue, self-efficac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…This finding agreed with Jin et al, (2021) (6) (25), focusing on "Improved perioperative quality of life in endoscopic sinus surgery by application of enhanced recovery after surgery," where it was reported that applying enhanced recovery after surgery led to an improved perioperative quality of life in endoscopic sinus surgery. These findings also concurred with He & He (2022) (26), who conducted a randomized controlled study on "Systematic nursing interventions in gastric cancer" and found that after applying the systematic nursing interventions, the scores in all aspects of quality of life within the observation group were significantly higher than those in the control group. These outcomes substantiate the third research hypothesis.…”
Section: Discussionsupporting
confidence: 85%
“…This finding agreed with Jin et al, (2021) (6) (25), focusing on "Improved perioperative quality of life in endoscopic sinus surgery by application of enhanced recovery after surgery," where it was reported that applying enhanced recovery after surgery led to an improved perioperative quality of life in endoscopic sinus surgery. These findings also concurred with He & He (2022) (26), who conducted a randomized controlled study on "Systematic nursing interventions in gastric cancer" and found that after applying the systematic nursing interventions, the scores in all aspects of quality of life within the observation group were significantly higher than those in the control group. These outcomes substantiate the third research hypothesis.…”
Section: Discussionsupporting
confidence: 85%
“…In patients with pancreatitis, the trypsin in the pancreas is activated, leading to edema and bleeding in the tissues around the pancreas, and even produce necrotic inflammatory reactions, which seriously reduces the life quality of patients[ 13 , 14 ]. In addition to clinical treatment, scientific nursing intervention is equally important, while the nursing intervention alone cannot achieve an ideal effect[ 15 , 16 ]. Therefore, on the basis of standardized nursing, more comprehensive and high-quality intervention measures should be taken.…”
Section: Discussionmentioning
confidence: 99%
“…Self-efficacy affects the quality of life of gastric cancer survivors, and it is one of the resources that should be assessed in patients before implementing interventions to improve the quality of life of gastric cancer survivors [18]. A study by He and He showed the positive importance of nursing interventions for perioperative gastric cancer patients based on education, psychological support taking into account the individuality of perioperative gastric cancer patients for improving their sense of self-efficacy, self-care ability, and quality of life [28]. In this study, the respondents obtained a score indicating an average level of disease acceptance.…”
Section: Discussionmentioning
confidence: 99%